Gone wolf - McBride, Amber (Feiwel and Friends, an imprint of Macmillan Publishing Group, LLC, 2023)
In the future, a Black girl known only as Inmate Eleven is kept confined--to be used as a biological match for the president's son, should he fall ill. She is called a Blue--the color of sadness. She lives in a small room with her dog, who is going wolf more often--he's pacing and imagining he's free. Inmate Eleven wants to go wolf too. She wants to know why she feels so Blue and what is beyond her small room. In the present, Imogen lives outside of Washington DC. The pandemic has distanced her from everyone but her mother and her therapist. Imogen has intense phobias and nightmares of confinement. Her two older brothers used to help her, but now she's on her own, until a college student helps her see the difference between being Blue and sad, and Black and empowered.